DIAGNOSTICS OF OSTEOPOROSIS IN PATIENTS WITH DEFORMING DISEASES OF LOWER EXTREMITIES’ LARGE JOINTS AND SPINE - E. G. Ippolitova; E. S. Tsyslyak; T. K. Verkhozina (Acta Biomedica Scientifica)
With the purpose of studying of bone tissue state at the degenerative dystrophic changes of musculoskeletal system, of the 3—4th degree densitometry with use of ultrasonic densitometer Sunlight Omnisens was carried out in preoperative period, in patients in the age from 50 to 72 years. These patients had. diskogenic lumbosacral radiculitis, one-sided. L—St radiculoneuritis, one-sided, degenerative coxarthrosis of the III degree and one-sided deforming gonarthrosis of the III degree. As the results in examined, groups of patients high percent of osteoporosis and ostheopenia was revealed. It was registered that intensity of osteoporotic changes on diseased. and. healthy extremities was different and. to a greater extent they showed, up on a diseased, extremity. This data confirmed, opportunities of ultrasonic densitometer Sunlight Omnisens to diagnose of ostheoporosis at earlier stages.